2019
DOI: 10.1002/hfm.20805
|View full text |Cite
|
Sign up to set email alerts
|

Calf massager: Intervention for body muscle discomfort during prolonged standing

Abstract: Many occupations require workers to stand for long periods of time without proper interventions, which causes discomfort in the back and lower limbs. Therefore, this study aims to assess the effectiveness in alleviating body muscle discomfort during prolonged standing through the use of a calf massager. This study was conducted among male workers at a manufacturer with production line workers and the list was obtained from the HR Department and simple random sampling was done by number categorization. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The study by Lee et al had also showed a decrease in HRV, cortisol and norepinephrine levels, although the changes did not recur 2 weeks after the end of study for all parameters except for the norepinephrine level. Yang et al [67] Wang et al [66] and Ramalingam et al [65] investigated the use of local vibration massage on pain management. The results were derived from questionnaires exhibited gradual improvement of pain perception throughout the study period.…”
Section: Effects On Psycho-physiological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Lee et al had also showed a decrease in HRV, cortisol and norepinephrine levels, although the changes did not recur 2 weeks after the end of study for all parameters except for the norepinephrine level. Yang et al [67] Wang et al [66] and Ramalingam et al [65] investigated the use of local vibration massage on pain management. The results were derived from questionnaires exhibited gradual improvement of pain perception throughout the study period.…”
Section: Effects On Psycho-physiological Variablesmentioning
confidence: 99%
“…However, the study also reported absence of any significant difference between massage group and vibration group on ROM (range of motion) and level of CK (creatine kinase). In another study by Anna et al [65], the effect of lower limb vibration on cyclist is documented. In this study, the authors applied vibration for 60 min after exercise, and reported a gradual decrease in blood lactate level as well as significant difference in other biochemical markers (IL-6, Mb, MMP-2) in experimental groups after intervention.…”
mentioning
confidence: 97%
“…For example, a device which apply pressure and massaging to the target muscle may increase blood flow to provide O2 to the working muscles. Researchers also suggest that treatment methods such as heat therapy, massage, and nutritional supplements can help with muscle fatigue alleviation [24][25][26][27][28].…”
Section: Background Of Fatiguementioning
confidence: 99%
“…Mental fatigue cannot be measured physically. Therefore, most of the studies utilize questionnaire surveys to examine subjective mental fatigue [9,10,28]. Besides, some may utilize the body part symptom survey form, or the visual analog scale in their surveys so that it will be clearer.…”
Section: Measurement Of Fatiguementioning
confidence: 99%
See 1 more Smart Citation